Measuring Fintech's Health: Cash Management and Risk on Firm Performance - Champaca, Mychelia (Universitas Brawijaya, Indonesia, 2024)
The development of financial institutions is in line with the massive development of the internet and technology, so the growth of fintech financial institutions is currently still an interesting topic to discuss. Most research on fintech uses a qualitative approach; this is because the topic of fintech is still in its early stages of development. By using a quantitative approach, this research makes a different contribution, namely by measuring the performance of fintech in Indonesia as a study of the context of developing countries. In addition, most research on fintech is still in the form of definitions and ecosystems of fintech financial institutions. Studies on fintech performance are still limited; this is explained by access to fintech financial report databases that have not been published standardly. This study examines the health of fintech financial institutions by looking at their influence on cash management and corporate riskiness. Studies included testing peer-to-peer lending fintech companies registered with the OJK and making observations during 2019-2022. The analysis method used was ordinary least squares regression from panel data. The results of the study show that there is no influence of cash holdings on company performance. A significant influence is shown by the negative influence of risk using the solvency ratio, although when measured using the liquidity ratio, the results are not significant. The test results prove the role of transactional motives in cash management for fintech companies in Indonesia.